The Relationship between Anxiety state and phobia with achievement among elite boxers - Ali, Mahdi (Journal of Physical Education, 2008)
The aim of study is to identify the relationship between state anxiety and phobia with achievement. Subjects were thirty – five elite boxers represented. The fist class clubs during 2005 – 2006. The study used phobia scale and sport anxiety scale for both positive and negative anxiety. Result showed a high negative correlation between phobia and achievement N T. also there was the same high correlation between anxiety and achievement in contest. The study recommended training with concentration on difficulties recovery for better performance